2019
DOI: 10.1038/s41467-019-09778-7
|View full text |Cite
|
Sign up to set email alerts
|

An inner activation gate controls TMEM16F phospholipid scrambling

Abstract: Transmembrane protein 16F (TMEM16F) is an enigmatic Ca 2+ -activated phospholipid scramblase (CaPLSase) that passively transports phospholipids down their chemical gradients and mediates blood coagulation, bone development and viral infection. Despite recent advances in the structure and function understanding of TMEM16 proteins, how mammalian TMEM16 CaPLSases open and close, or gate their phospholipid permeation pathways remains unclear. Here we identify an inner activation gate, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 47 publications
(66 reference statements)
12
91
0
Order By: Relevance
“…We note that the observed movement of TMs 3-6 is similar to the previously proposed "clam shell" model of TMEM16F activation. 17 However, the degree of TMs movement is smaller in TMEM16A compared to that of TMEM16F lipid scramblase (e.g., see Fig. 1D).…”
Section: Specific Pip2 Binding To Ca 2+ -Bound Tmem16a Induces Spontamentioning
confidence: 88%
See 4 more Smart Citations
“…We note that the observed movement of TMs 3-6 is similar to the previously proposed "clam shell" model of TMEM16F activation. 17 However, the degree of TMs movement is smaller in TMEM16A compared to that of TMEM16F lipid scramblase (e.g., see Fig. 1D).…”
Section: Specific Pip2 Binding To Ca 2+ -Bound Tmem16a Induces Spontamentioning
confidence: 88%
“…3,7 Our previous study of TMEM16F lipid scramblase has suggested a conserved "clam-shell" model of activation for the TMEM16 family proteins. 17 Whether a TMEM16 protein has channel and/or scramblase activities is likely determined by how wide the same pore may be dilated (e.g., see Fig. S1), as governed by the balance of interactions at the pore and various allosteric regulatory sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations